Breastfeeding and risk of overweight and obesity at nine years of age - MC CRORY, CATHAL; LAYTE, RICHARD (My University, 2012)
Whether breastfeeding is protective against the development of childhood overweight and obesity remains the subject of considerable debate. Although a number of meta-analyses and syntheses of the literature have concluded that the greater preponderance of evidence indicates that breastfeeding reduces the risk of obesity, these findings are by no means conclusive. The present study used data from the Growing Up in Ireland study to examine the relationship between retrospectively recalled breastfeeding data and contemporaneously measured weight status for 7,798 children at nine years of age controlling for a wide range of variables including, socio-demographic factors, the child?s own lifestylerelated behaviours, and parental BMI. The results of the multivariable analysis indicated that being breastfed for between 13-25 weeks was associated with a 38 percent (p<.05) reduction in the risk of obesity at nine years of age, while being breastfed for 26 weeks or more was associated with a 51 percent (p<.01) reduction in the risk of obesity at nine years of age. Moreover, results pointed towards a dose-response patterning in the data for those breastfed in excess of 4 weeks. Possible mechanisms conveying this health benefit include slower patterns of growth among breastfed children, which it is believed, are largely attributable to differences in the composition of human breast milk compared with synthesised formula. The suggestion that the choice of infant feeding method has important implications for health and development is tantalising as it identifies a modifiable health behaviour that is amenable to intervention in primary health care settings and has the potential to improve the health of the population.
PUBLISHED
Keywords: Ireland; breastfeeding; children; overweight; obesity; body mass index (BMI); cohort study